Assessment of predisposing factors and prescribing pattern in coronary artery disease patients at a tertiary care hospital of Southern Rajasthan - Purohit, Ayushi; Sharma, Sourabh (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Coronary artery disease (CAD) is the leading cause of mortality globally. The risk factors for the development of cardiovascular disease include lifestyle changes, diabetes mellitus, hypertension, smoking, hyperlipidemia, obesity and psychosocial stress. Drug regime plays an important role in declining the untimely deaths and enhances the quality of life. Few studies have been done on the prescribing patterns of CAD; hence the main objective of the study was to scrutinize various risk factors and therapy patterns for CAD patients. Methods: A non-interventional prospective study was conducted among 120 patients, to assess the risk factors and prescribing pattern in CAD patients. Information regarding patients was recorded in data collection form. Data was statistically analyzed using IBM statistical package for the social sciences (SPSS) software. Results: Majority of the patients were male (77.5%). Most of the patients (59.20%) were in age range of 50-69 years. Most common co-morbidities found were hypertension and diabetes. Body mass index (BMI), tobacco chewing, smoking were major risk factors. Majorly prescribed drugs were antiplatelets, anticoagulants, statins, antibiotics, nitrates, antihypertensive, PPI’s and analgesics. Average number of drugs encountered per prescription was 8.70. While number of encounters with a drug indicated in CAD was 5.66. Number of drugs prescribed with an injection and generic name were 4 and 1 respectively. As per DDD calculation, Heparin was consumed in highest amount. Conclusions: Polypharmacy was practiced. Generic prescribing was low. Major risk factors included BMI, tobacco chewing, smoking, diabetes and hypertension. Findings of this study can be used to develop a framework for ongoing prescription assessment in a healthcare setting.